Risk of aspiration pneumonia in paediatric patients with dysphagia who were found to have laryngeal penetration on the instrumental swallow evaluation: a systematic review protocol. Issue 8 (3rd August 2021) - Adlakha, Vaishali; Ramos, Leona; Smith, Abigail; Tsistinas, Olivia; Tanner-Smith, Emily; Merrow, Jill; Soultan, Zafer; Mortelliti, Anthony; Rosen, Rachel; Imdad, Aamer
Abstract : Introduction: Dysphagia affects several children in USA and around the globe. Videofluoroscopic Swallow Study (VFSS) and Fiberoptic Endoscopic Evaluation of Swallowing (FEES) are the most objective studies to define swallowing function. The presence of tracheal aspiration during VFSS or FEES in children with dysphagia is associated with an increased risk of aspiration pneumonia. However, the association of laryngeal penetration with aspiration pneumonia remains unclear. This systematic review aims to assess the risk of aspiration pneumonia in children with dysphagia with laryngeal penetration on VFSS/FEES and compare it with children with tracheal aspiration and children with neither tracheal aspiration nor laryngeal penetration. Methods and analysis: This study will be a systematic review and meta-analysis. Systematic electronic searches will be conducted on PubMed, EMBASE, Web of Science, CINHAL, Scopus, Cochrane CENTRAL, LILACS and WHO Global Index Medicus. We will include studies published through 6 October 2021. Primary outcome will be the incidence of aspiration pneumonia. Secondary outcomes will be incidence of hospitalisation, paediatric intensive care unit admission, enteral tube requirement, growth, symptoms improvement and mortality. The Cochrane Risk of Bias In Non-Randomised Studies of Interventions tool will be used to assess the risk of bias. Meta-analysis will be used to pool the studies. We will pool dichotomous outcomes to obtain an odd ratio (OR) and report with 95% CI. Continuous outcomes will be pooled to obtain mean difference and reported with 95% CI. Overall grade of evidence will be assessed using Grading of Recommendations Assessment, Development and Evaluation (GRADE) criteria, and findings will be presented in a summary of findings table. Ethics and dissemination: This study is a systematic review without contact with patients. Therefore, IRB approval is not required. Authors consent to publishing this review. Data will be kept for review by editors and peer reviewers. Data will be available to general public on request. PROSPERO registration number: CRD42020222145.